2020
DOI: 10.1177/1476718x20969841
|View full text |Cite
|
Sign up to set email alerts
|

Theorising child well-being: Towards a framework for analysing Early Childhood Education policy in England

Abstract: ‘Well-being’ is increasingly used in child rights discourses and early childhood education (ECE) policy contexts as a desirable outcome for young children. In spite of its ubiquitous use, however, child well-being remains largely under-theorised, thereby contributing to implicit understandings within policy arenas. This paper contributes to attempts to address this gap by proposing a theoretical framework of child well-being. The framework is developed in stages. First, two prominent approaches to well-being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Implementation research is defined as "the scientific study of methods to promote the systematic uptake of proven clinical treatments, practices, organizational, and management interventions into routine practice, and hence improve health" (37). Robust implementation research has the potential to mitigate the epidemic of paediatric chronic disease (7), advance research into early child development (24), and fast track evidence of the effectiveness and implementation of familycentred models of care that have been developed (7). However, evidence to determine the core elements of implementation theories, models and frameworks for paediatric research and practice and how these frameworks can be adapted to embed equity is first needed to meet this objective (38,39).…”
Section: Approaches Priorities and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation research is defined as "the scientific study of methods to promote the systematic uptake of proven clinical treatments, practices, organizational, and management interventions into routine practice, and hence improve health" (37). Robust implementation research has the potential to mitigate the epidemic of paediatric chronic disease (7), advance research into early child development (24), and fast track evidence of the effectiveness and implementation of familycentred models of care that have been developed (7). However, evidence to determine the core elements of implementation theories, models and frameworks for paediatric research and practice and how these frameworks can be adapted to embed equity is first needed to meet this objective (38,39).…”
Section: Approaches Priorities and Methodsmentioning
confidence: 99%
“…Work is needed to identify progress in children's participation in these initiatives which has been acknowledged as difficult due to a lack of monitoring data particularly at a country level (21). The meaning of health and well-being (and related concepts like quality of life and participation) to children and their families is another area that requires theoretical elucidation which has been reported as under-developed (24,25). The ramifications of this evidence gap are that if the conceptual meaning of terms including health and well-being (and related terms) are unknown or inadequately defined, measures used in research cannot be assumed to be valid or compared across studies (25).…”
Section: Participationmentioning
confidence: 99%
“…T Street (2020) states that documents which regulate work in early childhood education (ECE) settings mostly start from the discourse of children's rights emphasizing children's wellbeing as a desired outcome. This approach is visible in the curricula of early and preschool education of different countries, for example Aistear (NCCA, 2009), Te Whariki (Ministry of Education, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…
Over several decades, a policy framework focusing on child well-being improvement has emerged as one of the development goals (Bain et al, 2018;Coll-Seck et al, 2019;Hug et al, 2019). Yet, the lack of shared agreement on the child well-being concept and how best to measure it has limited its ability to achieve the expected outcomes (Biggeri & Cuesta, 2021;Street, 2021). Understanding the dynamics of child well-being, however, is crucial to the provision of better social facilities and improving the basic needs of children for effective transition from childhood to adulthood.Scholarly knowledge concerning child well-being was built on Western and developed countries' experience (Bradshaw et al, 2007(Bradshaw et al, , 2013D'Agostino et al, 2019;Idoiaga Mondragon et al, 2021), which has been found to be of little relevance in explaining child well-being in the Southeast Asia context (Cho, 2015).
…”
mentioning
confidence: 99%
“…Over several decades, a policy framework focusing on child well-being improvement has emerged as one of the development goals (Bain et al, 2018;Coll-Seck et al, 2019;Hug et al, 2019). Yet, the lack of shared agreement on the child well-being concept and how best to measure it has limited its ability to achieve the expected outcomes (Biggeri & Cuesta, 2021;Street, 2021). Understanding the dynamics of child well-being, however, is crucial to the provision of better social facilities and improving the basic needs of children for effective transition from childhood to adulthood.…”
mentioning
confidence: 99%